Amino acid sequence of a putative sodium channel expressed in the giant axon of the squid Loligo opalescens. - Rosenthal, J J (1993)
A full-length cDNA encoding a putative Na+ channel (GFLN1) has been cloned from a library prepared from the stellate ganglion of Loligo opalescens. The cDNA encodes a predicted protein of 1784 amino acids. Regions of the GFLN1 protein with defined functional importance (membrane span S4, the SS1 and SS2 segments, and interdomain III-IV) are highly conserved among all vertebrate Na+ channel alpha-subunit structures. Northern blot hybridization and RNase protection assays verify that mRNA corresponding to GFLN1 is expressed in neurons of the giant fiber lobe that form the giant axon. We propose that GFLN1 encodes the Na+ channel that has been extensively studied in the squid axon.